Successfully Stifling Retroperitoneal and Pelvic Exsanguination by Resuscitative Endovascular Balloon Occlusion of the Aorta in a Rural Setting - Bonnici, Maximilian; Knight Davis, Jennifer (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Background: Torso hemorrhages are increasingly controlled by transient employment of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). Few studies report patients’ conditions after the initial resuscitation period using REBOA, especially in a rural setting. We present a highly successful 1-year post-operative recovery using REBOA for retroperitoneal and pelvic exsanguination. Methods: A 36-year-old female suffered a constellation of traumatic injuries after being ejected from her motorcycle. She arrived at a rural level 1 trauma center shortly thereafter. Results: REBOA was employed to control profuse hemorrhaging and the patient had a highly resilient recovery after one year. A literature review was conducted to highlight the points of contention regarding the controversial use of REBOA. Conclusion: REBOA can produce favorable results with minimal long-term deficits when controlling pelvic exsanguination.